Primary Intravitreal Bevacizumab (Avastin) for Diabetic Macular Edema Results from the Pan-American Collaborative Retina Study Group at 6-Month Follow-up (2007)
Purpose: To report the 6-month anatomic and best-corrected visual acuity (BCVA) response after primary intravitreal bevacizumab (Avastin) in patients with diabetic macular edema (DME). Design: Interventional retrospective multicenter study at 6 centers from 6 countries of patients with DME. Participants: We reviewed the clinical records of 88 consecutive patients (110 eyes) with DME. Seventyeight eyes of 64 consecutive patients with a minimum follow-up of 6 months and mean age of 59.7 9.3 years were included in this analysis